Potential Mechanisms Linking Food-Derived MicroRNAs, Gut Microbiota and Intestinal Barrier Functions in the Context of Nutrition and Human Health - Díez-Sainz, Ester; Lorente-Cebrián, Silvia; Aranaz, Paula; Riezu-Boj, José I.; Martínez, J. Alfredo; Milagro, Fermín I. (Frontiers in Nutrition, 2021)
MicroRNAs (miRNAs) are non-coding single-stranded RNA molecules from 18 to 24 nucleotides that are produced by prokaryote and eukaryote organisms, which play a crucial role in regulating gene expression through binding to their mRNA targets. MiRNAs have acquired special attention for their potential in cross kingdom communication, notably food-derived microRNAs (xenomiRs), which could have an impact on microorganism and mammal physiology. In this review, we mainly aim to deal with new perspectives on: 1) The mechanism by which food-derived xenomiRs (mainly dietary plant xenomiRs) could be incorporated into humans through diet, in a free form, associated with proteins or encapsulated in exosome-like nanoparticles. 2) The impact of dietary plant-derived miRNAs in modulating gut microbiota composition, which in turn, could regulate intestinal barrier permeability and therefore, affect dietary metabolite, postbiotics or food-derived miRNAs uptake efficiency. Individual gut microbiota signature/composition could be also involved in xenomiR uptake efficiency through several mechanisms such us increasing the bioavailability of exosome-like nanoparticles miRNAs. 3) gut microbiota dysbiosis has been proposed to contribute to disease development by affecting gut epithelial barrier permeability. For his reason, the availability and uptake of dietary plant xenomiRs might depend, among other factors, on this microbiota-related permeability of the intestine. We hypothesize and critically review that xenomiRs-microbiota interaction, which has been scarcely explored yet, could contribute to explain, at least in part, the current disparity of evidences found dealing with dietary miRNA uptake and function in humans. Furthermore, dietary plant xenomiRs could be involved in the establishment of the multiple gut microenvironments, in which microorganism would adapt in order to optimize the resources and thrive in them. Additionally, a particular xenomiR could preferentially accumulate in a specific region of the gastrointestinal tract and participate in the selection and functions of specific gut microbial communities.